Evaluation of socialization technology effectiveness in motor-play activity of preschoolers - Serykh, Larisa V.; Voloshina, Lyudmila N.; Kondakov, Viktor L.; Buchek, Albina A. (Linguistics and Culture Review, 2021)
Motor-play activity is the basis for the social experience recreation and development among older preschoolers, a condition for positive socialization. The relevance of the research is conditioned by the need to comprehend the potential of socialization technology in motor-game activity of preschoolers. The use of technology in the educational process at kindergartens contributes to the complex impact on a child, the development of his physical, social, communicative and personal potentials. The purpose of the study is to assess the effectiveness of socialization technology in motor-play activity among 5-7-year-old children. Study methods: theoretical: analysis, synthesis, generalization; empirical: observation and assessment of independent motor activity among children, game diagnostic situations, conversation; the methods of mathematical statistics: Wilcoxon t-test. The study involved 120 senior preschool children attending the kindergarten No. 78 in the city of Belgorod, No. 15 in the village of Razumnoe, Belgorodsky District, Belgorod Region. The analysis of the study results showed that in the process of socialization technology implementation in motor-play activity among preschoolers, 95% of children who participated in the experiment use successfully the social experience in motor-play activity and show the optimal and sufficient level of its recreation.